Adherence, exposure and patients’ experiences with the use of erlotinib in non-small cell lung cancer - Timmers, Lonneke (J Cancer Res Clin Oncol, 2015)
PURPOSE: Erlotinib is an orally administered tyrosine kinase inhibitor used for treatment of non-small cell lung cancer. Understanding actual use of medication is essential for optimizing treatment conditions. METHODS: In this multicentre prospective observational study, patients starting erlotinib treatment were followed for 4 months. Adherence was assessed using a medication event monitoring system (MEMS). Area under the curve (AUC) was determined after 1, 2 and 4 months. Before start and at monthly intervals, patients filled out questionnaires about attitude towards medication and disease, quality of life, symptoms and use in daily practice. RESULTS: Sixty-two patients (median age 63.5 years, 53 % male) were included of whom 15 were still on treatment after 4 months. MEMS data of 55 patients revealed a mean adherence of 96.8 ± 4.0 %. Over one-third of patients had an adherence rate <95 %. At 1 month, 21 % of patients did not always correctly take erlotinib without food. Associated risk factors were older age, suboptimal adherence, ocular symptoms and stomatitis (all p < 0.05). After 1 month of treatment, fatigue (91 %) and rash (86 %) were the most common symptoms reported. AUC(ss) of erlotinib was higher in patients with rash and patients with moderate–severe anorexia (both p < 0.05). CONCLUSION: Though adherence to erlotinib treatment is generally high, non-adherence might be an issue in a considerable number of patients. To support optimal erlotinib intake, clinicians need to take adequate measures to ameliorate symptoms and to address adherence and correct intake without food. Especially older patients and those who experience stomatitis may need extra attention.